Ome aspects related to the transformation of the three body wave function built on the Gaussian basis - B. A. Urazbekov; A. S. Denikin; N. .. Itaco; N. T. Tursunbayev (Eurasian Journal of Physics and Functional Materials, 2021)
The three-body wave function built on the basis of the Gaussian function, calculated using the three-body Hamiltonian with the Pauli blocking operator is studied. As an example, the wave function of the ground state of the 9 Be was taken. Analytical expressions are presented for the overlap matrix elements of the basis function for both basic and alternative set of relative Jacobi coordinates. The correlation densities of the wave function are calculated and illustrated depending on the set of orbital quantum numbers.